Degradasi Limbah Zat Warna Direk Dengan Metode Advanced Oxidation Processes (AOPs) Kombinasi H2O2/MnO2 dengan Parameter Uji BOD, COD dan pH - Venitalitya Alethea Sari Augustia; Inggit Dwi Lestari; Maulita Dian Rani (Eksergi, 2018)
Advanced Oxidation Processes (AOPs) method has been applied and is growing in number of textile wastewater treatment. Textile industries are commonly using synthetic dyes in the dyeing process and will produce coloured-wastewater that is still contain of organic compound and is hard to be degraded. One of most frequently used synthetic dyes in textile industries is direct dyes. Direct dyes wastewater consists of azo bound whereby difficult to eliminate the colour and the concentration itself, thus an appropriate treatment such as AOPs is considered. The AOPs process to degrade direct dyes wastewater in this research uses a combination of H2O2 with catalyst MnO2. Parameter variation that carried out, are the variation of the ratio of wastewater and H2O2 volume, namely 1:1; 2:1 and 1:2. Whilst the using of mass of catalyst MnO2 is 1 g for each sample variation, namely 1 g for 250 ml and 500 ml H2O2. The results obtained after the BOD, COD and pH tests, are 230 mg/l, 784 mg/l and 5,26 respectively. This result is showed by the sample with variation 2:1 which is delivering the lowest values of BOD, COD and pH amongst the three sample variations mentioned